What history says about the constitution, development and fall of Nazi Germany - Plath, Rafael de Sousa (Revista Terra & Cultura: Cadernos de Ensino e Pesquisa; Vol 38 No 75 (2022): jul./dez., 2022)
Nazi Germany was not born overnight, nationalist and revanchist ideals due to the defeat in World War I, the Economic Crisis in the United States that affected Europe in reconstruction, the class struggle between communists and Nazis in the 1920s and 1930s, the devaluation of the German currency, the strong opposition between the proletarians and the bourgeoisie contributed decisively to the formation and strengthening of the National Socialist German Workers' Party, which in the future would reach power in the country through its supreme leader, Adolf Hitler, starting a series of persecution to the regime's opponents such as communist writers and ethnic minorities, such as Jews, for example, culminating with the beginning of the Second World War with the German invasion of Poland. During the time when the war was concentrated against France, England and countries smaller in military importance, the axis Germany, Italy and Japan remained firmly in the conflict. However, from 1942 onwards, with the entry of the United States and the Soviet Union on the side of the Allies, the war began to take a different course, putting into decline Hitler's imperialist ambitions and, finally, his defeat in 1945. It is about this process of rise, development and fall of Nazi Germany that this work intends to discuss, summarizing excerpts extracted from literature used in elementary and secondary education in Brazilian public education in recent years.